A Study of the Effect of TPU and Clay Nanoparticles on the Mechanical Behavior of PBT-Based Nanocomposites - Ata Chalabi Tehran; Karim Shelesh-Nezhad; Pouya Faraji Kalajahi; Ali Olad (Mechanics of Advanced Composite Structures)
In this research, thermoplastic polyurethane (TPU) and clay nanoparticles were incorporated into poly (butylene terephthalate) (PBT) to improve the impact and tensile properties. The PBT/TPU (90/10, 80/20 and 70/30) samples were prepared by melt mixing using a co-rotating twin-screw extruder followed by injection molding. At the next stage, clay nanoparticles of different weight fractions were added to the PBT/TPU (80/20) blend in the same way to prepare nanocomposite samples. SEM images illustrated good compatibility between TPU and PBT. To characterize the dispersion of clay layers in the polymer matrix, wide-angle X-ray diffraction (WAXD) inspections were performed. The results of the mechanical assessments showed that the addition of TPU to PBT significantly increased the impact strength but decreased the tensile strength and modulus. Incorporating clay nanoparticles into the PBT/TPU blend noticeably improved the tensile properties of PBT/TPU-based nanocomposites. A balance of the tensile and impact properties was found in the PBT/TPU/clay (80/20/3) nanocomposite system.